Newly arrived refugees' perception of health and physical activity in Denmark - Knud Ryom; Camilla Bakkær Simonsen; Stefan Runge Rau; Helle Terkildsen Maindal; Sine Agergaard (Elsevier, 2022)
Refugees health status after receiving asylum in their new country is often poor, both physical and mentally. Despite that, European countries rarely offer programmes specifically targeted health and health behaviour for newly arrived refugees. This study investigated newly arrived refugees' perspective on health and in particularly physical activity (PA) upon granted asylum in Denmark. A transnational migration perspective provides the theoretical framework in this study. Semi-structured interviews with twenty newly arrived refugees provide data for the interpretative phenomenological analysis (IPA). Health manifests itself in varied ways to the newly arrived refugees and a broad and holistic perspective on health, was evident. Overall PA had important benefits, such as pain relief, better physical fitness, lose weight, a stronger body, to stay active, cater to mental health and in general something of interest to the newly arrived refugees. However, the informants experienced several barriers for doing PA and living healthy lives. Time, pain, low income, job insecurity, mental strain, discourse of health and PA (health promotion), external expectations and demands (municipality and government in Denmark), precariat living conditions and general worrying were amongst the most explicit barriers. Based on the results, we underline the importance of involving refugees in developing health promotion activities while considering of their unique experiences and transnational background.